2019
DOI: 10.1101/821835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Torsin ATPases are required to complete nuclear pore complex biogenesis in interphase

Abstract: 32Nuclear envelope herniations (blebs) containing FG-nucleoporins and ubiquitin are the 33 phenotypic hallmark of Torsin ATPase manipulation. Both the dynamics of blebbing and the 34 connection to nuclear pore biogenesis remain poorly understood. We employ a proteomics-based 35 approach to identify MLF2 as a luminal component of the bleb. Using an MLF2-based live cell 36imaging platform, we demonstrate that NE blebbing occurs rapidly and synchronously 37 immediately after nuclear envelope reformation during mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Based on studies in human cells, mice and Drosophila, diverse roles of Torsins have been suggested, including functions in ER homeostasis, secretion, lipid metabolism, NPC biogenesis, and the nuclear export of large particles like mRNPs or HSV1 capsids by a vesicular transport process across the NE (Chen et al, 2010, Grillet et al, 2016, Jokhi et al, 2013, Maric et al, 2011, Nery et al, 2011, Pappas et al, 2018, Rampello et al, 2019, Shin et al, 2019, Turner et al, 2015. However, while all these suggested functions are supported by the reported cellular phenotypes, biochemical and genetic data, it is currently unclear what are direct or indirect consequences of Torsin function since the molecular mechanism of Torsin action has remained elusive.…”
Section: The Torsin-lap1 Interplaymentioning
confidence: 99%
“…Based on studies in human cells, mice and Drosophila, diverse roles of Torsins have been suggested, including functions in ER homeostasis, secretion, lipid metabolism, NPC biogenesis, and the nuclear export of large particles like mRNPs or HSV1 capsids by a vesicular transport process across the NE (Chen et al, 2010, Grillet et al, 2016, Jokhi et al, 2013, Maric et al, 2011, Nery et al, 2011, Pappas et al, 2018, Rampello et al, 2019, Shin et al, 2019, Turner et al, 2015. However, while all these suggested functions are supported by the reported cellular phenotypes, biochemical and genetic data, it is currently unclear what are direct or indirect consequences of Torsin function since the molecular mechanism of Torsin action has remained elusive.…”
Section: The Torsin-lap1 Interplaymentioning
confidence: 99%
“…Upon Torsin manipulation, interphase assembly is stalled presumably prior to the fusion of the inner nuclear membrane (INM)/outer nuclear membrane (ONM). Note that cytoplasmic fibrils (CFs) containing NUP358 are only added to the nascent NPC after INM/ONM fusion during interphase assembly (i.e., the observed absence of NUP358 from blebs containing NPC components supports the idea of blebs representing stalled NPC assembly intermediates) [32,84].…”
Section: The Role Of Torsin Atpases In Nuclear Pore Biogenesismentioning
confidence: 89%
“…While there is accumulating evidence indicating that Torsins contribute a critical function in NPC biogenesis, their precise role in this molecular pathway remains largely unknown. The recent finding that the loss of TorsinA and its three paralogs in HeLa cells results in a stalling of interphase assembly provides new insight into this mode of NPC assembly [32]. The formation of Nup-containing NE blebs follows a cell cycle-dependent growth and loss pattern, with an increase in the number during interphase and a substantial reduction following mitosis (Figure 3).…”
Section: Torsins Atpases Contribute To Npc Assembly During Interphasementioning
confidence: 96%
See 2 more Smart Citations